The Effect of Charismatic Leadership, Financial Compensation, and Employment Training on PT Telkom Balikpapan Operational Performance - Hermin Nainggolan (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of the influence of charismatic leadership, financial compensation, and job training on the operational performance of PT. Telkom Access Balikpapan either partially or simultaneously. The population in the study amounted to 331 employees. The sample of this study was 76 employees of PT. Telkom Access Balikpapan, which is still actively working, was selected by using a random sampling technique. The method used is quantitative method, data collection is carried out using primary data through direct questionnaires to respondents. Data were analyzed with validity and reliability tests, as well as multiple linear regression analysis t test, f test, using the SPSS VERSION 26.0 program. The results of this study indicate that: The first hypothesis is obtained by Charismatic Leadership, Financial Compensation, and Job Training simultaneously have a positive and significant effect on the Operational Performance of PT. Telkom Access Balikpapan Second hypothesis. Charismatic Leadership (X1) partially has a positive and significant influence on the Operational Performance of PT. Telkom Access Balikpapan. Hypothesis three. Financial Compensation (X2) partially has a positive and significant effect on the Operational Performance of PT. Telkom Access Balikpapan. Hypothesis four. Job Training (X3) partially has a positive and significant impact on the Operational Performance of PT. Telkom Access Balikpapan.